2019
DOI: 10.1002/fut.21990
|View full text |Cite
|
Sign up to set email alerts
|

Institutional quality and sovereign credit default swap spreads

Abstract: We examine how the quality of political, legal, and regulatory institutions impacts sovereign risk premia. An improvement in institutional quality significantly lowers a country's sovereign credit default swap (CDS) spread, even after controlling for domestic and global macroeconomic factors. The incremental effect of institutional quality may also be economically important in explaining the variations in the level of sovereign CDS spreads. The basic results are robust to alternative model specifications, samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
(130 reference statements)
0
3
0
Order By: Relevance
“…The smallest cluster on default swaps and monetary policy contains 57 articles cited 497 times. Articles related to default swaps deal with the credit default swap premia (Benkert, 2004), the sensitivity of collateralized debt obligations (Meneguzzo & Vecchiato, 2004), pricing and integration of credit default swaps (Carverhill & Luo, 2020), risk in bank default swaps (Huang, 2020), credit default swap spreads (Huang et al, 2019), and credit risk (Elkamhi et al, 2012). Articles on monetary policy include predictors of monetary policy (Krueger & Kuttner, 1996) and the effect of monetary policy on stocks and commodities (Basistha & Kurov, 2015; Vähämaa & Äijö, 2011).…”
Section: Bibliographic Coupling Of Jfm Articlesmentioning
confidence: 99%
“…The smallest cluster on default swaps and monetary policy contains 57 articles cited 497 times. Articles related to default swaps deal with the credit default swap premia (Benkert, 2004), the sensitivity of collateralized debt obligations (Meneguzzo & Vecchiato, 2004), pricing and integration of credit default swaps (Carverhill & Luo, 2020), risk in bank default swaps (Huang, 2020), credit default swap spreads (Huang et al, 2019), and credit risk (Elkamhi et al, 2012). Articles on monetary policy include predictors of monetary policy (Krueger & Kuttner, 1996) and the effect of monetary policy on stocks and commodities (Basistha & Kurov, 2015; Vähämaa & Äijö, 2011).…”
Section: Bibliographic Coupling Of Jfm Articlesmentioning
confidence: 99%
“…Still, it should be noted that political factors play a significant role in Türkiye since many political risks, such as political upheavals, ethnic conflicts, religious tensions and terror incidents, are constantly on the agenda. Therefore, assessments taking into account these concepts (Gün et al, 2016;Balding, 2011;Huang et al, 2019;Akkaya & Kanar, 2017;Bozkurt & Kaya, 2018;Ulusoy & Kendirli, 2019) are also reviewed within this study. Among these, Gün et al (2016) take into account the Gezi Park Protests of 2013; Akkaya and Kanar (2017) focus on Türkiye's downing of Russian warplane and the coup d'état attempt on 15 th July; Bozkurt and Kaya (2018) assess the news coming from the Arabian Peninsula and Ulusoy and Kendirli (2019) scrutinise the terrorist attacks in Türkiye to investigate the effects of political developments on CDS premia.…”
Section: Introductionmentioning
confidence: 99%
“…According to the findings, negative jumps have stronger influences on CDS spreads than positive jumps. Huang, Lin, & Yang (2019) investigated whether the qualities of political, legal and regulatory institutions affect the CDS premium for 70 countries over the period 2000-2015. According to the research results, it was concluded that high corporate quality is associated with lower country risk which is suggesting that institutional quality has a role in explaining sovereign CDS spreads. Ersan & Günay (2009) tested whether the closure case against the ruling party in March 2008 in Turkey has a statistically significant effect on Turkey's CDS using daily data for the period 2004-2009, and they found no significant relationship.…”
Section: Introductionmentioning
confidence: 99%